2002
DOI: 10.1038/sj.cgt.7700461
|View full text |Cite
|
Sign up to set email alerts
|

Tumor gene therapy by MVA-mediated expression of T-cell–stimulating antibodies

Abstract: Immune responses to tumor -associated antigens are often dampened by a tumor -induced state of immune anergy. Previous work has attempted to overcome tumor -induced T -cell anergy by the direct injection of vectors carrying the genes encoding one of a variety of cytokines. We hypothesised that the polyclonal stimulation of T cells, preferably through the TCR complex, would result in a cascade of cytokines associated with T -cell activation and would be best able to overcome T -cell anergy. Here we use the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…We and others have previously shown that cells modified to express chimeric anti-CD3 receptors can activate naive T cells. [15][16][17] Expression of anti-CD3 surface receptors should reduce the dependency of T-cell activation on MHC expression, allowing effective therapy by CD80 or CD86 in poorly immunogenic tumors that are normally refractive to modification with costimulatory molecules.…”
mentioning
confidence: 99%
“…We and others have previously shown that cells modified to express chimeric anti-CD3 receptors can activate naive T cells. [15][16][17] Expression of anti-CD3 surface receptors should reduce the dependency of T-cell activation on MHC expression, allowing effective therapy by CD80 or CD86 in poorly immunogenic tumors that are normally refractive to modification with costimulatory molecules.…”
mentioning
confidence: 99%
“…Currently, the most promising approaches are based on replication-competent agents that allow efficient tumour penetration. Exciting results are anticipated with poxviruses [10, 11] and with selectively replicating/targeted adenoviruses [12, 13, 14, 15, 16], although pre-clinical models suggest that significant response rates will only be achieved by combination with standard therapies.…”
Section: Vectors (Table 1)mentioning
confidence: 99%
“…Vaccinia virus infects all cells, however the host immune response to the vector does not abrogate the tumour immune response even following repeated injections. The availability of attenuated virus ( tk - modified vaccinia ankara ) [10] allows the use of vaccinia in immuno-delicate cancer patients and there is evidence that this vector enhances immunological rejection of the tumour.…”
Section: Vectors (Table 1)mentioning
confidence: 99%
“…Expression levels are relatively low and transient, but for some purposes such as targeted introduction of toxin genes or siRNA, this may prove to be a useful vector system because of its ease of use, lack of antigenicity, and apparent safety (no integration, no inflammation). 44 A number of other viruses have been used over the past several years for gene therapy, including Newcastle Disease Virus (see above), vaccinia virus for tumor antigen expression, 45 and other orthopoxviruses, such as canarypox. 46 For nonviral delivery systems, most progress has been made using variations of lipofection.…”
Section: Vectors and Gene Delivery Systemsmentioning
confidence: 99%